Software engineering based secured E-payment system - Muayad Sadik Croock; Rawan Ali Taaban (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Nowadays, the E-payment systems have been considered to be the safe way of money transfer in most of modern institutes and companies. Moreover, the security is important side of these systems to ensure that the money transfer is done safely. Software engineering techniques are used for guaranteeing the applying of security and privacy of such systems. In this paper, a secure E-payment system is proposed based on software engineering model and neural network technology. This system uses different proposed algorithms for applying authentication to the devices of users as mobile application. They are used to control the key management in the system. It uses the neural network back-propagation method for ensuring the security of generated keys that have sufficient random levels. The proposed system is tested over numerous cases and the obtained results show an efficient performance in terms of security and money transfer. Moreover, the generated keys are tested according to NIST standards.